STUDENTS’ RESPONSE TOWARDS THE IMPLEMENTATION OF FOREIGN INSTRUCTOR PROGRAMME IN HELPING WITH STUDENT’S SPEAKING SKILL - Muhammad Aldhi Bagustha Utama; Bahrul Ulum; Winarsih (Universitas Islam Balitar, 2023)
The purpose of this study is to describe students’ response on how effective it is in hiring professional native English speakers in helping new learners to master their speaking skill. Foreign instructors can not only help in improving the speaking skill of the beginners, but they can also help to modify the optimal learning environment that can familiarise the beginners in the learning activities they are doing. Foreign professionals who are proposed to educate beginners must master teaching skill and be good at using 21st century technology. In this research paper, the experimental method is used to study this experiment. The main purpose is to find out if hiring native English speakers is very effective in helping beginners to master their speaking skills. The results found show that hiring a professional native English speaker is very effective in helping beginners in mastering speaking skills because in addition to the knowledge gained, speaking with a native English speaker directly helps beginners in speaking English.